2019
DOI: 10.1111/fwb.13444
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term variability and density dependence in Hudson River Dreissena populations

Abstract: We used a 27-year record of Dreissena populations in the freshwater tidal HudsonRiver to describe interannual variation in population density, body size, and body condition; estimate long-term variation in recruitment, survivorship, and shell growth; and assess possible controls on the populations. 2.Dreissena populations in the Hudson have been highly variable, with interannual ranges of c. 100-fold in abundance and biomass, and 7-fold in mean body mass. This large interannual variation arises from both long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…For many sessile species, such as mussels, competition for both space and food can lead to decreased growth and survival rates (Fréchette et al., 1992; Strayer et al. 2020). Although many retrospective analyses have explored density‐dependent processes, few studies have accounted for uncertainty about the strength and form of density dependence in population forecasts (but see Colchero et al., 2009; Reed et al., 2013) or assessed how interactions between population density and climate could affect future population trajectories.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For many sessile species, such as mussels, competition for both space and food can lead to decreased growth and survival rates (Fréchette et al., 1992; Strayer et al. 2020). Although many retrospective analyses have explored density‐dependent processes, few studies have accounted for uncertainty about the strength and form of density dependence in population forecasts (but see Colchero et al., 2009; Reed et al., 2013) or assessed how interactions between population density and climate could affect future population trajectories.…”
Section: Figurementioning
confidence: 99%
“…Density-dependent processes are known to be important mechanisms driving rates of population change when species depend on one or more limited resources (Turchin, 1995). For many sessile species, such as mussels, competition for both space and food can lead to decreased growth and survival rates (Fréchette et al, 1992;Strayer et al 2020). Although many retrospective anal- This exploration of the different ways in which density-dependent processes could affect population forecasts of blue mussels provided insights that would have been overlooked had analyses simply relied on the best-supported model for population forecasts.…”
mentioning
confidence: 99%
“…None of the 42 longer-term (>10 year) data series on adult dreissenid mussels from Europe and North America analyzed by Strayer et al [15] showed a differential decline of quagga mussels, and there was no general decline in the combined dreissenid mussels with time since invasion. But only four of these 42 data sets included more than 10 years of annual data on adult mussels from systems with both quagga and zebra mussels (Oneida Lake [12], Hudson River [75], Lake Balaton [54], and Onondaga Lake-this study). Interestingly, in the Hudson River, quagga mussels have remained subdominant for decades, perhaps due to higher predation rates in the river [75].…”
Section: Plos Onementioning
confidence: 99%
“…But only four of these 42 data sets included more than 10 years of annual data on adult mussels from systems with both quagga and zebra mussels (Oneida Lake [12], Hudson River [75], Lake Balaton [54], and Onondaga Lake-this study). Interestingly, in the Hudson River, quagga mussels have remained subdominant for decades, perhaps due to higher predation rates in the river [75]. There are also studies that were not included in the Strayer et al data set that suggest a link between predator abundance and mussel species dominance.…”
Section: Plos Onementioning
confidence: 99%
“…Although the water in the study area is fresh, rarely with even a trace of sea salt, the entire study area is strongly tidal, with tidal amplitudes of 0.8–1.6 m, and daily tidal flows usually are much greater than net downriver flows. Zebra mussels first appeared in the Hudson in 1991, and the population has been large but variable since autumn 1992 (Strayer et al., 2020).…”
Section: Methodsmentioning
confidence: 99%